EFONI DAN KAKOFONI DALAM PUISI-PUISI WASIAT CINTA (Euphony and Cacophony in the Poems “Wasiat Cinta”) - Besse Darmawati (Balai Bahasa Sulawesi Selatan, 2014)
Literary works have value as literary if it implies poetic aspects. This research aims to describe the poetic aspects in the poems Wasiat Cinta analyzed by euphony and cacophony. Due to the aim, the writer applies qualitative method through intuitive and analytic approach. The techniques of this research are reading-listening, classification, and content analysis. The data of this research are the poems Air Laut Terbang Bersama Dua Matahari by Asia Ramli Prapanca, Kata Cinta Usia 51 and Selalu Ada Laut by Badaruddin Amir. Those poems are written in Wasiat Cinta: Mimbar Penyair Makassar book, published by Nala Cipta Litera in 2013. Based on the result of the analysis, it is found that the poems (1) Air Laut Terbang Bersama Dua Matahari contains euphonic elements to make the pronunciation and rhythm enunciated smoothly, and describes the atmosphere of pleasant situation and the happy meaning; (2) Kata Cinta Usia 51 contains cacophonic elements to obstruct the pronunciation and rhythm lines, describes the bad situation and the atmosphere of regret meaning; (3) Selalu Ada Laut contains euphonic elements show in the harmony and cacophonic elements that disorganize the previous harmony, then both of them should be synchronized with patience and strong belief to harmonize them.